Economic Security – A Principal Component of Multilevel Security Concept in Global Economy - Alexander Kelisek; Jozef Klucka; Milos Ondrusek; Stanislava Strelcova (Communications - Scientific letters of the University of Zilina, 2011)
This paper is focused on the problem of the economic security as the principal component of a multilevel security concept in the present global economy. The authors characterize various theoretical and practical notions of security as the complex phenomenon. The economic security as an integral component of the mentioned security concept is also characterized. The further text is concentrated on the global aspects of economic security, which are depicted in the examples in economies of China, the U.S.A. and the EU.